Eliciting Psychological Ownership of Object by Marking Organizational Name: The Role of Belongingness - Wang, Wenhua; Pierce, Jon L.; Li, Dahui; Wang, Guangrong; Li, Jianbiao; Niu, Xiaofei (Frontiers in Psychology, 2021)
Psychological ownership critically entails the need for Home (a place in which to dwell or a place of belongingness). However, the question of how an individual’s need for belongingness within an organization affects their psychological ownership of organization-linked objects remains unexplored. We first conducted a behavioral study to determine whether psychological ownership of object can be elicited by marking the object with the name of the subjects’ organization. The participants in this behavioral study reported a higher level of psychological ownership when objects were marked with their own organization’s name (i.e., in-organization objects) compared with objects marked with another organization’s name (i.e., out-organization objects). Importantly, this effect was more pronounced among subjects who experienced a stronger sense of organizational belongingness. We subsequently conducted a second study to explore its underlying neural mechanism. Our findings indicated that participants with a higher level of perceived organizational belongingness exhibited a significantly larger amplitude of the P300 component of event-related potential in response to in-organization objects compared with their response to out-organization objects. However, no significant difference in the P300 component was found for participants who lacked a sense of organizational belongingness.